The FDA approved PI3K inhibitor GDC‐0941 enhances in vitro the anti‐neoplastic efficacy of Axitinib against c‐myc‐amplified high‐risk medulloblastoma. Issue 4 (29th January 2018) - Ehrhardt, Michael; Craveiro, Rogerio B.; Velz, Julia; Olschewski, Martin; Casati, Anna; Schönberger, Stefan; Pietsch, Torsten; Dilloo, Dagmar
Abstract: Aberrant receptor kinase signalling and tumour neovascularization are hallmarks of medulloblastoma development and are both considered valuable therapeutic targets. In addition to VEGFR1/2, expression of PDGFR α/β in particular has been documented as characteristic of metastatic disease correlating with poor prognosis. Therefore, we have been suggested that the clinically approved multi‐kinase angiogenesis inhibitor Axitinib, which specifically targets these kinases, might constitute a promising option for medulloblastoma treatment. Indeed, our results delineate anti‐neoplastic activity of Axitinib in medulloblastoma cell lines modelling the most aggressive c‐myc‐ amplified Non‐WNT/Non‐SHH and SHH‐ TP53 ‐mutated tumours. Exposure of medulloblastoma cell lines to Axitinib results in marked inhibition of proliferation and profound induction of cell death. The differential efficacy of Axitinib is in line with target expression of medulloblastoma cells identifying VEGFR 1/2, PDGFR α/β and c‐kit as potential markers for drug application. The high specificity of Axitinib and the consequential low impact on the haematopoietic and immune system render this drug ideal multi‐modal treatment approaches. In this context, we demonstrate that the clinically available PI3K inhibitor GDC‐0941 enhances the anti‐neoplastic efficacy of Axitinib against c‐myc‐ amplified medulloblastoma. Our findings provide a rational to further evaluate Axitinib alone and in combination with other therapeutic agents for the treatment of most aggressive medulloblastoma subtypes.